Lanostane- and cycloartane-type triterpenoids from Abies balsamea oleoresin - Lavoie, Serge; Gauthier, Charles; Legault, Jean; Mercier, Sylvain; Mshvildadze, Vakhtang; Pichette, André (Beilstein Journal of Organic Chemistry, 2013)
Phytochemical analysis of A. balsamea oleoresin led to the isolation of three new 3,4-seco-lanostane triterpenoids 1–3, one new cycloartane triterpenoid 4 along with fourteen known terpenoids. Structure determinations were based on extensive 1D/2D NMR, IR and MS spectroscopic analyses, and comparison with literature data. The isolated compounds were evaluated in vitro for their cytotoxicity against human cell lines (A549, DLD-1, WS1) and their antibacterial activity against E. coli and S. aureus. Abiesonic acid (6) exhibited weak cytotoxic activity against A549 (IC50 = 22 µM) while compounds 1 and 4 were weakly active against S. aureus (MIC = 25 µM).
Keywords: Abies balsamea; cycloartane; lanostane; oleoresin; triterpenoids